Description of Massilia rubra sp. nov., Massilia aquatica sp. nov., Massilia mucilaginosa sp. nov., Massilia frigida sp. nov., and one Massilia genomospecies isolated from Antarctic streams, lakes and regoliths - Holochová, Pavla; Mašlaňová, Ivana; Sedláček, Ivo; Švec, Pavel; Králová, Stanislava; Kovařovic, Vojtěch; Busse, Hans-Jürgen; Staňková, Eva; Barták, Miloš; Pantůček, Roman (Systematic and applied microbiology, 2020)
Bacteria of the genus Massilia often colonize extreme ecosystems, however, a detailed study of the massilias from the Antarctic environment has not yet been performed. Here, sixty-four Gram-stain-negative, aerobic, motile rods isolated from different environmental samples on James Ross Island (Antarctica) were subjected to a polyphasic taxonomic study. The psychrophilic isolates exhibited slowly growing, moderately slimy colonies revealing bold pink-red pigmentation on R2A agar. The set of strains exhibited the highest 16S rRNA gene sequence similarities (99.5-99.9%) to Massilia violaceinigra B2T and Massilia atriviolacea SODT and formed several phylogenetic groups based on the analysis of gyrB and lepA genes. Phenotypic characteristics allowed four of them to be distinguished from each other and from their closest relatives. Compared to the nearest phylogenetic neighbours the set of six genome-sequenced representatives exhibited considerable phylogenetic distance at the whole-genome level. Bioinformatic analysis of the genomic sequences revealed a high number of putative genes involved in oxidative stress response, heavy-metal resistance, bacteriocin production, the presence of putative genes involved in nitrogen metabolism and auxin biosynthesis. The identification of putative genes encoding aromatic dioxygenases suggests the biotechnology potential of the strains. Based on these results four novel species and one genomospecies of the genus Massilia are described and named Massilia rubra sp. nov. (P3094T=CCM 8692T=LMG 31213T), Massilia aquatica sp. nov. (P3165T=CCM 8693T=LMG 31211T), Massilia mucilaginosa sp. nov. (P5902T=CCM 8733T=LMG 31210T), and Massilia frigida sp. nov. (P5534T=CCM 8695T=LMG 31212T).
Keywords: geologické sedimenty; Genes, rRNA; Phenotype; Massilia; Whole-genome sequence; Antarctica; jezera; DNA bakterií; bakteriální geny; Psychrophilic bacteria; RNA, Ribosomal, 16S; DNA, Bacterial; Rivers; Genome, Bacterial; genom bakteriální; Polyphasic taxonomy; Phylogeny; Antarktida; Antarctic Regions; řeky; Bacterial Typing Techniques; Sequence Analysis, DNA; techniky typizace bakterií; Geologic Sediments; Genes, Bacterial; geny rRNA; Lakes; fenotyp; sekvenční analýza DNA; Oxalobacteraceae; fylogeneze; RNA ribozomální 16S